"It was a terrible, terrible journey": an instrumental case study of a spouse's experience of living with a partner diagnosed with semantic variant primary progressive aphasia. Issue 4 (3rd April 2017) - Pozzebon, Margaret; Douglas, Jacinta; Ames, David
ABSTRACT: Background : Semantic variant primary progressive aphasia (svPPA) is an uncommon neurodegenerative condition that causes prominent changes in communication skills, personality and behaviour. Insidious deterioration in conceptual–semantic memory abilities is the hallmark feature underpinning these impairments from the early-to-middle phases. Very little research has explored how svPPA is experienced by spouses/partners, particularly how they "make sense" of the presenting difficulties, deal with everyday issues and manage the changing psychosocial aspects of their intimate relationship. Aims : This instrumental case study explored the experience of a spouse who supported her husband with svPPA throughout the course of the condition, with a particular focus on how she dealt with the relational changes svPPA imposed on them. Methods & Procedures : Instrumental case study design with thematic narrative analysis was applied to the in-depth interview data, in order to obtain an understanding of the lived experience from the perspective of a wife whose husband had svPPA. Outcome & Results : Analysis of the interview data revealed five main themes of the spousal experience of svPPA: (1) Us, (2) The way he was … The way he is now, (3) Floundering with unpredictability, (4) Adjusting and accepting support and (5) Taking control. This case study explored how and why this spouse worked towards renegotiating the relational context of their relationship over the illness course. Conclusions : From the spouse's perspective, learning to live with a "different person" was traumatic and involved floundering with unpredictability, adjusting and accepting support, and taking control. Clinicians need to remain sensitive to the pivotal role the spouse has in their partner's life and mindful of that they may benefit from assistance and support to modify the relational aspects of their relationship with their partner throughout the course of the condition.